Legal Aspects of Medical Malpractice: Patient Protection and Physician Liability - Tuti Herningtyas; Endah Labati; Anna Veronica Pont (Universitas Muhammadiyah Palu, 2025)
Medical malpractice represents a significant violation within healthcare services, posing serious risks to patient safety and eroding public trust. In Indonesia, incidents of malpractice are relatively frequent, yet many remain unresolved due to limited legal awareness and inadequate access to justice for patients. This article examines the legal dimensions of medical malpractice by focusing on two critical aspects: the legal protection afforded to patients and the legal liability borne by medical practitioners. Employing a normative juridical approach, alongside an analysis of relevant legislation and case studies, this paper aims to provide a comprehensive understanding of the existing legal frameworks and the practical challenges faced in their enforcement. The findings are expected to serve as a valuable reference for stakeholders, including patients, healthcare professionals, and legal institutions.